KELAYAKAN BISNIS PUPUK ORGANIK PADA CV DHARMA PERTIWI, KELURAHAN LUKLUK, KABUPATEN BADUNG - Muhammad Hanzah Firdausi; Putu Fajar Kartika Lestari; Ni Putu Anglila Amaral, (AGRIFARM (Jurnal Agribisnis dan Sosial Ekonomi Pertanian), 2024)
Dharma Pertiwi is a company that operates in the field of making organic fertilizer, making fertilizer, getting capital from bank loans and getting support for raw materials from several Gapoktan in Bali. This research aims to calculate business income and analyze business efficiency. The data collection method used in this research is observation, interviews, questionnaires, literature study and documentation during research at CV. Dharma Pertiwi, Lukluk Village, Badung. The respondents in this research are the owners of the CV company. Dharma Pertiwi with the data used, namely data on production income and fertilizer production. The results of this research show that there are large profits in the production of organic fertilizer at CV. Dharma Pertiwi where higher profits are obtained from total production costs in the 2021-2022 period. Meanwhile, the resulting efficiency level is 1.1 in the 2021-2022 period, where the efficiency value is more than 1 and is said to be quite efficient in the organic fertilizer production process at CV. Dharma Pertiwi, Lukluk Village, Badung. In the production process there are also obstacles faced, such as: Insufficient marketing to increase consumers and strategies in developing the company, distribution permits that have not been made to market the product because making the letter requires large costs to meet the criteria for making a distribution permit, such as feasibility tests, fertilizer resistance tests, and other feasibility tests, promotions have not been maximized only around the production site, because the distribution permit has not yet been issued.